1998
DOI: 10.1161/01.atv.18.7.1124
|View full text |Cite
|
Sign up to set email alerts
|

Platelet GP IIIa Pl A and GP Ib Variable Number Tandem Repeat Polymorphisms and Markers of Platelet Activation in Acute Stroke

Abstract: Abstract-A number of polymorphisms of the platelet glycoprotein (GP) Ib-V-IX and IIb/IIIa complexes have been described, and the Pl A polymorphism of GP IIIa has been associated with coronary thrombosis. We determined the levels of ␤-thromboglobulin (␤-TG) and platelet factor 4 (PF4) and the genotype distributions of Pl A and a variable number tandem repeat (VNTR) polymorphism of GP 1b in subjects with acute stroke (nϭ609) and healthy control subjects (nϭ435). Levels of ␤-TG were higher in patients both initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 41 publications
2
97
1
1
Order By: Relevance
“…HPA polymorphisms are associated with stroke; heterozygosity for the GP 3a A2 allele is a risk factor for atherosclerotic stroke in young individuals, and the HPA3 b/b polymorphism and homozygosity for the HPA1b polymorphism are associated with ischemic stroke (65)(66)(67). However, HPA polymorphisms are not associated with hemorrhagic stroke, and the GP 3a A2 allele is not a risk for myocardial infarction, stroke, or venous thrombosis (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…HPA polymorphisms are associated with stroke; heterozygosity for the GP 3a A2 allele is a risk factor for atherosclerotic stroke in young individuals, and the HPA3 b/b polymorphism and homozygosity for the HPA1b polymorphism are associated with ischemic stroke (65)(66)(67). However, HPA polymorphisms are not associated with hemorrhagic stroke, and the GP 3a A2 allele is not a risk for myocardial infarction, stroke, or venous thrombosis (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…27 In one of these studies, the genotype effect of the PlA1/A2 polymorphism was more obvious among women, 28 and in the other study, the genotype effect was stronger in nonsmokers. 23 Thus the relative contribution of genetic factors might differ significantly, depending on the populations analyzed. This might in part explain the conflicting results of the published studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 Subsequently, several studies were reported, but only a few studies focused on the association of this genotype with stroke, and the results were not consistent. [21][22][23] Therefore we performed an allelic association study to compare genotype frequencies between CVD patients and age-and sex-matched control subjects.…”
mentioning
confidence: 99%
“…The PL A2 polymorphism has been identi®ed in 10À21% of the Caucasian population [38À41]. The presence of the PL A2 allele has been associated with increasing platelet sensitivity to platelet agonists [42] and has been proposed as a hemostatic risk factor associated with arterial thrombotic disease [38,43] and neurological damage [39,44,45]. The reported allele frequency is similar to the frequency of donors exhibiting HIPA, and a DNA analysis was performed using a previously published protocol [41] to determine if a correlation between the PL A2 allele and HIPA exists.…”
Section: Pl A2 Allelementioning
confidence: 99%